(untitled) (Medico Legal Update, 2020)
Background:Demirjian’s technique of age assessment based on tooth development stages has been extensively investigated in different populations of the world. Aim: The present study is to assess the applicability of Demirjian’s modified 8-teeth technique in age estimation of population of south India (kadapa) Materials and Method: Two hundred pre-treatment orthodontic radiographs of patients in an age group of 10-20 years with representation from both genders were assessed for eight left mandibular teeth and scored as per the Demirjian’s criteria. Statistical analysis was performed to compare the estimated and actual age. Results: The results revealed that the mean value in age estimation of the entire sample was 1.39years. The Mean value in males and females (10–20years) was 1.33and 1.46 respectively.Conclusion: significant positive co relationwith estimating dental age in which chronological age is higher compared to dental age.